Y-5x=1Y+3x=9

Simple and best practice solution for Y-5x=1Y+3x=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-5x=1Y+3x=9 equation:



-5Y=1+3Y=9
We move all terms to the left:
-5Y-(1+3Y)=0
We add all the numbers together, and all the variables
-5Y-(3Y+1)=0
We get rid of parentheses
-5Y-3Y-1=0
We add all the numbers together, and all the variables
-8Y-1=0
We move all terms containing Y to the left, all other terms to the right
-8Y=1
Y=1/-8
Y=-1/8

See similar equations:

| 9x²-1=0 | | x^2-3x+39=0 | | 32=m | | 320=m | | 5(5y+5)=-100 | | (-4/3)y=-4/5 | | 5(x–1)–2x=3(x+7) | | 4(4y+-4)=0 | | y=39-2 | | 5/6(-3x-9)=-6 | | (2x)x=2¹² | | 2b–4=10 | | (1,2))x+1=(3,2))x-8 | | x^2-3x^2=160 | | (x-1)/5=(x-1)2 | | 3x-5=3x+5. | | 4x+2=5x-1. | | (10x-5)÷5=-7+12 | | 5(5n+2)=235 | | 3w+7=31 | | (2.77^(-x))*x=0.2 | | 7m+0=-42 | | 2(y=4)=16 | | -6m+7=67 | | 72n–6=1 | | 2(y+10)=16 | | 68=-4-9x | | 1x+-1=-9 | | (x^2+8x+16)(x^2-8x+16)=0 | | 50=5x(+5) | | 0.85*200=0.7*a | | 0.85x+0.05(18-x)=0.10(-103) |

Equations solver categories